2014
DOI: 10.1007/s11250-014-0742-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pathogens of subclinical mastitis in dairy goats in China

Abstract: Subclinical mastitis, a costly disease for the dairy industry, is usually caused by intramammary bacterial infection. The aim of this study was to investigate the prevalence of and pathogens involved in subclinical mastitis in dairy goats in China. A total of 683 dairy goats in the main breeding areas of China were selected, and milk samples were collected. Out of these, 313 (45.82 %) goats were detected distinct or strong positive for subclinical mastitis by using California mastitis test. Among these positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
1
18
0
7
Order By: Relevance
“…These results are too great extent in accord with previous studies, where staphylococci were recorded to be the most prevalent bacteria in cases of mastitis and account for 90% of isolated bacteria [10,49-51]. Furthermore, CNS recorded to have the capability of increasing SCC in goat milk and occur at over 50% in most studies of goat SCM [47]. About streptococci, it was reported to be the major pathogens for their severe inflammation, but they are less common in SCM in goats [47].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…These results are too great extent in accord with previous studies, where staphylococci were recorded to be the most prevalent bacteria in cases of mastitis and account for 90% of isolated bacteria [10,49-51]. Furthermore, CNS recorded to have the capability of increasing SCC in goat milk and occur at over 50% in most studies of goat SCM [47]. About streptococci, it was reported to be the major pathogens for their severe inflammation, but they are less common in SCM in goats [47].…”
Section: Resultssupporting
confidence: 79%
“…In a recent study carried out in China, SCM was diagnosed in 45.82% of examined dairy goats [47], while it was 18% in Sweden [13] and 30.2% in India [48]. The authors attributed this high prevalence of SCM to be attributed to poor milking hygiene and the less awareness of SCM impact.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding mastitis, similar frequencies of clinical mastitis (less than 5%) and clinical or subclinical IMI etiology to the present study were reported in the review by Bergonier et al (2003) based on large-scale surveys in European goat breeds. Others reported similar SCS levels and varying prevalence (15-80%) of subclinical mastitis in Indian (Mishra et al, 2018), Spanish (Contreras et al, 1999), or Chinese goats (Zhao et al, 2015). In general, previous studies have reported the definite predominance of CNS, such as S. epidermidis and S. chromogenes, as causal agents of subclinical and often chronic mastitis.…”
Section: Can These Results Be Extended To Field Situations?mentioning
confidence: 86%
“…dysagalactia and Strep uberis, respectively. [19], 40.5% in 42 first partum Santa Ines ewes in Brazil [20] and 45.8% among goats in China [21] were previously recorded. Higher prevalence rates of 66.9% in Awassi sheep in Jordan [22] and 61% among goats in Kenya [23] were previously reported.…”
Section: Amplification Of Gsag Gsdys and Gsub Genes Of Streptococcusmentioning
confidence: 99%